Persepsi Mahasiswa Pendidikan Matematika FKIP Universitas Mataram Terhadap Pembelajaran Daring di Era Covid-19 - Nurdianti Nurdianti; Sudi Prayitno; Amrullah Amrullah; Nani Kurniati (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to determine the perception of mathematics education students of FKIP Unram on the online learning process, abilities after online learning, and to describe related to online learning in the covid-19 era in mathematics education students of FKIP Unram in the 2020/2021 academic year. This research was carried out using descriptive qualitative research methods, for data collection a questionnaire was distributed via google form, with a sample of mathematics education students who were active and learning online in the 2020/2021 academic year. The instrument used in this study is a closed questionnaire, where respondents just choose the answers that are already available. The results showed that the perception of students of the Mathematics Education Study Program FKIP Unram towards the online learning process in the 2020/2021 academic year was categorized as good with a percentage of 79.13%. Meanwhile, students' perceptions of abilities after online learning are in good category with a percentage of 70.44%. Based on the results of the percentage scores for each indicator of the perception of the online learning process and the ability after online learning, there are several things that must be maintained and developed in online learning at the Unram Mathematics Education Study Program, namely 1). Lecturers always provide learning materials or materials. 2). The material provided by the lecturer is in the form of modules or textbooks. 3). The material presented online is in accordance with the lecture/RPS contract. 4). The online learning process is carried out using the Google Meet application. 5). Students find it easier to use the Google Meet application in the online learning process. 6). Students always do the assignments given by the lecturer. 7). Lecturers always check student attendance. 8). Lecturers give additional value to students who actively ask and answer in the online learning process. 9). Lecturers always provide opportunities for students to ask questions and discuss. 10). Lecturers respond to questions that arise during the online lecture process. 11). Lecturers provide feedback by asking students questions related to the material that has been studied.